Empowering OTOP MSMEs through Digital Marketing Literacy for Global Market Access - Dwi Hardiana, Candra; Syafei, M. Yani; Lestari, Novi; Andriani, Diana; Putri Iswahyudi, Dina Azizah; Irawan, Nico; Adikusuma Dai, Karnadi; Rosmiyanti, Yanti (CV. Inara, 2025)
This international community service program aimed to empower OTOP MSMEs in Samut Prakan, Thailand, by strengthening their digital marketing literacy as a pathway to global market access. Conducted on August 26, 2025, at the Bang Prong Subdistrict Administrative Organization Office, the program was a collaboration between the Doctoral Study Program in Management Science, Universitas Komputer Indonesia, and the Thai Global Business Administration Technological College. The activities included product exhibitions, production process demonstrations, and digital marketing workshops focusing on branding, social media content creation, and international promotion strategies. Evaluation through pre- and post-training surveys indicated significant improvements in three dimensions: understanding of digital marketing, ability to create engaging online content, and confidence in accessing global markets. Participants also reported enhanced entrepreneurial confidence and awareness of global market requirements. The findings highlight that digital marketing literacy is not merely a technical skill but a strategic driver for global competitiveness and cultural sustainability. This program demonstrates that community-based, cross-border collaborations can effectively equip entrepreneurs with the knowledge and skills necessary to expand their reach into international value chains while preserving local identity. Keywords: OTOP, digital marketing literacy, MSMEs, global market access, community service.